2020
DOI: 10.1164/rccm.201904-0769oc
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rare SERPINA1 Variants on Lung Function and Emphysema in SPIROMICS

Abstract: Rationale: The role of PI (protease inhibitor) type Z heterozygotes and additional rare variant genotypes in the gene encoding alpha-1 antitrypsin, SERPINA1 (serpin peptidase inhibitor, clade A, member 1), in determining chronic obstructive pulmonary disease risk and severity is controversial.Objectives: To comprehensively evaluate the effects of rare SERPINA1 variants on lung function and emphysema phenotypes in subjects with significant tobacco smoke exposure using deep gene resequencing and alpha-1 antitryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 45 publications
1
35
0
1
Order By: Relevance
“…xMAP technology has been applied to determine AAT concentration in different samples such as serum, plasma, urine, or sputum. Aside from AATD patients [ 28 ], it has also been used to measure AAT concentration, along with other molecules, as a biomarker of disease severity in ulcerative colitis [ 29 ], long-term recovery of chronic disorder of consciousness [ 30 ], bladder cancer diagnosis signature [ 31 ], or inflammatory profile in chronic obstructive pulmonary disease [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…xMAP technology has been applied to determine AAT concentration in different samples such as serum, plasma, urine, or sputum. Aside from AATD patients [ 28 ], it has also been used to measure AAT concentration, along with other molecules, as a biomarker of disease severity in ulcerative colitis [ 29 ], long-term recovery of chronic disorder of consciousness [ 30 ], bladder cancer diagnosis signature [ 31 ], or inflammatory profile in chronic obstructive pulmonary disease [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several case–control studies indicated a higher prevalence of the PI*MZ genotype among patients with COPD compared with controls without COPD [ 31 33 ]. A recently published analysis of a large cohort of individuals with COPD showed that PI*Z heterozygotes with a significant cigarette smoking history are at an increased risk of COPD compared with ever-smoker PI*MM individuals, have lower lung function, greater airflow obstruction and greater computed tomography (CT)-based quantitative measures of emphysema [ 34 , 35 ]. These reports suggest that PI*MZ patients have a higher susceptibility to smoking-related lung disease.…”
Section: Main Textmentioning
confidence: 99%
“…For decades, the MZ genotype was considered to represent a "carrier" state. Recently however, an interaction between the MZ genotype and smoking has been shown to significantly increase the risk of COPD [5] and the severity of airflow obstruction relative to usual (MM) smokers [6,7]. Consequently, MZ AATD smokers represent a common, high-risk subgroup, with a genetically predetermined course toward greater morbidity.…”
Section: Introductionmentioning
confidence: 99%